A novel guanine-guanine base pairing: crystal structure of a complex between 7-methylguanosine and its iodide. - Yamagata, Y (1983)
7-Methylguanosine, one of the biologically important minor nucleosides, could be crystallized as a complex of its zwitterionic form and its iodide, and the crystal structure was determined by the X-ray diffraction method. The crystals belong to the triclinic space group P1 with the unit cell dimensions: a = 7.678(1), b = 18.094(3), and c = 5.711(1) A, alpha = 79.32(1), beta = 80.14(1) and gamma = 76.90(1) degrees. The structure was solved by the heavy atom method and refined by the least-squares method to give a final R index of 0.075. The novel reverse Watson-Crick type base pairing observed between a positively charged molecule and a deprotonated one indicates that the deprotonation at the N(1) position promoted by the alkylation at the N(7) position may interrupt the formation of the normal Watson-Crick type GC base pair. The conformations about the glycosidic bond and the sugar puckering are quite different between the two molecules: the former has anti and C(4')-exo,C(3')-endo and the latter syn and C(1')-exo-C(2')-endo.